Oral Motor Development in Children Aged 0-12 Months: A Review of Functional and Therapeutic Aspects - Emi Kuswanti; Imron Arifin; Pramono Pramono (Al-Qalam Institute, 2024)
This study examines oral motor development in children aged 0-12 months with a focus on functional and therapeutic aspects. The purpose of the study is to understand the pattern of oral motor development, influencing factors, and evaluate the effectiveness of various therapeutic methods applied. The qualitative research method was used by collecting data through in-depth interviews, participatory observations, and document analysis at school. The results of the study showed that the initial suction reflex and stimulation from the environment played an important role in oral motor development. Oral muscle exercises and the use of technology such as oral vibrators have been shown to be effective in strengthening the oral muscles, improving chewing and speaking skills in children. However, there is controversy regarding the use of therapeutic tools, with some parents and therapy professionals preferring the natural approach. This study emphasizes the importance of parental education and their active involvement in the therapy process for optimal outcomes. The implications of this study are the need for a holistic approach and timely interventions to support healthy oral motor development, as well as the importance of flexibility in choosing a therapy method that suits the specific needs of the child.